2021
DOI: 10.1007/s11768-021-00070-y
|View full text |Cite
|
Sign up to set email alerts
|

Brain–computer interfaces for human gait restoration

Abstract: In this review article, we present more than a decade of our work on the development of brain–computer interface (BCI) systems for the restoration of walking following neurological injuries such as spinal cord injury (SCI) or stroke. Most of this work has been in the domain of non-invasive electroencephalogram-based BCIs, including interfacing our system with a virtual reality environment and physical prostheses. Real-time online tests are presented to demonstrate the ability of able-bodied subjects as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…This is compatible with situations in which the participants in the present study presented a lower Ac CSP−LDA than usual, which contrasted with the more common situation where the activation of the interface occurred almost instantly. Similar findings were reported by Nenadic [24] and Liu [6].…”
Section: Success Percentage Of Fes S Activationsupporting
confidence: 91%
See 2 more Smart Citations
“…This is compatible with situations in which the participants in the present study presented a lower Ac CSP−LDA than usual, which contrasted with the more common situation where the activation of the interface occurred almost instantly. Similar findings were reported by Nenadic [24] and Liu [6].…”
Section: Success Percentage Of Fes S Activationsupporting
confidence: 91%
“…Performance gradually improved until reaching a more typical result for each of the participants. In Nenadic's study [24] it was found that participants take an average of four to five sessions to achieve their best performance. This suggests that performance may improve over time due to human-computer co-adaptation, and perhaps to other factors such as MI reactivation of dormant cortical areas.…”
Section: Success Percentage Of Fes S Activationmentioning
confidence: 99%
See 1 more Smart Citation